The effects of experimentally irradiated pituitary gland on the growth of rats’ tibia, skull, maxilla and mandible - Milosavljević, Željko; Krstić, Nikola (Vojnosanitetski pregled, 2021)
Background/Aim. The reaction of an organism to radiation depends on the level of irradiation and the sensitivity of the affected tissue cells. The biological effects on the cells and tissues are proportional to the absorbed radiation energy. The aim of our study was to examine the effects of hypofunction of the pituitary gland, previously irradiated with x-rays, on the growth of rat’s craniofacial and stomatognathic system as well as rat’s tibia. Methods. A total dose of x-rays of 27.92 Gy was applied in eight sessions in the period from 8 to 63 days of animal age on their heads and the effects of irradiation-induced hypofunction of the pituitary gland on the growth of rat’s craniofacial and stomatognathic system and tibia were examined. In order to differentiate the effects of the irradiated pituitary gland from the direct effects of x-rays on the head, the experiment was set as a double study. One group of animals had the pituitary gland protected with a lead plate set beneath the projection of the gland, while the second group was irradiated with the same dose, but without the protection. The control group of animals were non-irradiated. Results. Growth measurements of numerous parameters of the craniofacial and stomatognathic system as well as tibia in rats with the entire locally irradiated head showed a statistically significant delay, compared to both the non-irradiated control group and the group with the protected pituitary gland. Conclusion. The damage of the stomatognathic and craniofacial system was greater in animals with irradiated head without pituitary gland protection compared to those with the gland protection whereby the growth of the craniofacial system was most affected. Irraduition-induced pituitary gland hypofunction and irradiation itself showed a stronger effect on the lower jaw growth rate impairment compared to the upper jaw. Similarly, the delay in tibia growth was more pronounced in animals without pituitary gland protection during irradiation of their heads compared to non-protected ones.